EDUKASI KHASIAT DAUN SALAM SEBAGAI UPAYA PENINGKATAN PENGETAHUAN IBU RUMAH TANGGA - Shinta Mayasari (Universitas Haji Sumatera Utara, 2022)
Bay leaf (Syzygium polyanthum) was one of the plants that was easily founded in the yard of the house, but not many people knowed about the benefits of this plant. Education about the efficacy of bay leaves was very important to give to the public so that they were rich in knowledge of the efficacy of these plants. The purpose of this community service was to provide insight into knowledge that was more than bay leaves besides being used as a spice in everyday life. The method used in community service was online via online by discussing and asking questions directly to the community, especially housewives. The results obtained from community service activities are that housewives respond to the material presented so that they become more aware and understand the efficacy of bay leaves which have not been known as herbal plants. From the results of community service activities, it cold be concluded that housewives become more aware of and understand the efficacy of bay leaves other than as a spice, namely as a herbal plant that could reduce complaints from various diseases including diabetes mellitus, gout, cholesterol and so on.